Purse Seine Vessel Redesign: An Effort to Optimize Fishing Vessel Planning in Bulukumba Regency - Quraisyin, Muh. Iqbal (SIGANUS: Journal of Fisheries and Marine Science, 2024)
Traditional purse seine vessels typically do not meet shipping architecture or IMO standards. The purpose of this research is to evaluate the suitability of purse seine vessel design and redesign it to meet applicable standards. The research was conducted in December 2022 in Tana Lemo Village, Bontobahari District, Bulukumba Regency, South Sulawesi. The analysis started by evaluating the main dimensions and hydrostatic parameters for their suitability, followed by an assessment of static stability. Numerical methods and simulations from the Maxsurf V.8i program were used for the analysis, along with a comparison of the sample measurement results and the standard values for purse seine vessels. The analysis results indicate that the sample vessel did not meet the criteria for main dimensions and hydrostatic parameters. However, after the redesign, the static stability of the vessel increased and met the IMO standards. Therefore, it is necessary to adjust the height and width while maintaining the length of the vessel to meet the standard values of main dimensions, hydrostatic parameters, and stability.